2017
DOI: 10.5334/labphon.117
|View full text |Cite
|
Sign up to set email alerts
|

Context-dependent articulation of consonant gemination in Estonian

Abstract: The three-way quantity system is a well-known phonological feature of Estonian. In a number of studies it has been shown that quantity is realized in a disyllabic foot by the stressed-tounstressed syllable rhyme duration ratio and also by pitch movement as the secondary cue. The stressed syllable rhyme duration is achieved by combining the length of the vowel and the coda consonant, which enables minimal septets of CVCV-sequences based on segmental duration. In this study we analyze articulatory (EMA) recordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…This finding was consistent with data from various languages that suggested that the closing gesture for a geminate consonant starts earlier than for a singleton (e.g., Šimko et al, 2014, for Finnish, Türk et al, 2017, for Estonian, Ridouane & Hallé, 2017, for Tashlhiyt Berber; see review in §1). However, in other languages no effect of gemination on articulatory timing was found (e.g., Moroccan Arabic, according to Zeroual et al, 2008).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This finding was consistent with data from various languages that suggested that the closing gesture for a geminate consonant starts earlier than for a singleton (e.g., Šimko et al, 2014, for Finnish, Türk et al, 2017, for Estonian, Ridouane & Hallé, 2017, for Tashlhiyt Berber; see review in §1). However, in other languages no effect of gemination on articulatory timing was found (e.g., Moroccan Arabic, according to Zeroual et al, 2008).…”
Section: Discussionsupporting
confidence: 89%
“…Contextsensitivity is an important issue also in articulatory-kinematic studies. For instance, Šimko et al (2014) reported that the anticipation of the lip closing gesture for /p:/ in Finnish occurred in the /ap:i/ context more than in the /ip:a/ context and when the preceding consonant was /t/ more than when it was /p/; similar effects were found by Türk et al (2017) in Estonian. Features of the consonant are relevant also in Zeroual et al's (2008) and Ridouane and Hallé's (2017) studies, according to which linguopalatal contact and gestural velocity differences are significant for voiceless plosives but not for their voiced cognates.…”
Section: Aims Of the Current Studymentioning
confidence: 82%
See 1 more Smart Citation
“…Their data included an intervocalic /p/ in the context of /ɑ-i/ or /i-ɑ/ and the results indicated that a segmental-level influence sometimes outweighs the quantity itself. This was also shown by an articulatory study [23] that used the same set of material as [22] for investigating the kinematics of the articulatory gestures (gesture duration, spatial extent, peak velocity) in terms of the quantity distinction. The kinematic characteristics were mainly influenced by the quantity on the segmental level.…”
Section: Introductionmentioning
confidence: 77%
“…At this stage of the study, however, vocalic context effects were not considered. As [22], [23] have shown, the vocalic context influences the realization of the Estonian three-way quantity distinction; with this in mind, subsequent studies should also take the vocalic context effects into account.…”
Section: Discussionmentioning
confidence: 99%